Status report and future prospects on LUNASKA lunar observations with ATCA - James, C.; Ekers, Ronald; Alvarez-Muñiz, J.; Protheroe, R.; McFadden, R.; Phillips, C.; Roberts, P. (Elsevier, 2009)
LUNASKA (Lunar UHE Neutrino Astrophysics with the Square Kilometre Array) is a theoretical and experimental project developing the lunar Cherenkov technique for the next generation of giant radio-telescope arrays. Here we report on a series of observations with ATCA (the Australia Telescope Compact Array). Our current observations use three of the six 22 m ATCA antennas with a 600 MHz bandwidth at 1.2-1.8 GHz, analogue dedispersion filters to correct for the typical night-time ionospheric dispersion, and state-of-the-art 2 GHz FPGA-based digital pulse detection hardware. We have observed so as to maximise the UHE neutrino sensitivity in the region surrounding the galactic centre and to Centaurus A, to which current limits on the highest-energy neutrinos are relatively weak. Crown Copyright © 2009.